Seeding resilience: Building knowledge and capacity through relationships among Black and Indigenous women farmers - Emma Brinkmeyer; Gabrielle Roesch-McNally; Hannah Dankbar; Maritza Pierre; Erin Upton; Nicole Gwishiri; Ebonie Alexander; Carrie Martin; Grace Summers (Journal of Agriculture, Food Systems, and Community Development, 2025)
Black and Indigenous women farmers face concurrent complex challenges in their farming operations such as a changing climate, institutional discrimination, and a historic wealth gap. The compounding nature of these challenges provides opportunities for agricultural technical assistance providers to create innovative educational approaches to support and build capacity towards greater resilience. American Farmland Trust, North Carolina Extension, and Black Family Land Trust piloted a “Get Climate Smart Food and Agricultural System’s Resilience Training” with 30 Black and Indigenous women farmers in North Carolina during 2023 and 2024. The training’s focus was to engage historically underserved women producers to (a) actualize conservation skills and climate smart practices, including monitoring and implementation; (b) improve technical skills regarding diversifying production and marketing systems for greater economic and food system resilience; and (c) develop leadership and mentoring skills to build community and social resilience around food and agriculture. All sessions were structured using a learning circle model that fostered collaborative, participant-driven learning compared to traditional instructor-led sessions; enrolled participants engaged in virtual, in-person, asynchronous, and hands-on activities. After the program concluded, the team conducted 18 in-depth semi-structured interviews with a subset of participants. Findings revealed that the program’s learning circle model and cohort network were highly effective for beginning and experienced Black and Indigenous women farmers, particularly by sustaining relationships and implementing climate smart practices on their land beyond the program timeframe. This article will review the program’s model and discuss how this type of program and its learning outcomes foster social sustainability by boosting individual, farm-scale, and local food resilience.